Demographic and genetic characterization of harvested Corbicula fluminea populations - Wang, Weikai; Liu, Xiongjun; Ferreira-Rodríguez, Noé; Sun, Weiwei; Wu, Yanli; Ouyang, Shan; Zhou, Chunhua; Wu, Xiaoping (PeerJ, 2020)
The freshwater clam Corbicula fluminea s.l. is an edible freshwater bivalve of economic value in Asia. The species has been particularly well studied in the invaded range. However, there is a lack of knowledge in its native range where it supports an increasing commercial harvest pressure. Among Asiatic countries, China accounts for 70% of known commercial harvest and aquaculture production. We aim to characterize here wild C. fluminea s.l populations exposed to commercial harvest pressure in Poyang Lake Basin. We found higher biomass, density and genetic diversity in lake populations compared to peripheral populations (i.e., lake tributaries). Given that lake habitats support more intense harvest pressure than peripheral habitats, we suggest that demographic and genetic differentiation among subpopulations may be influenced in some degree by different harvest pressure. In this regard, additional demographic and/or genetic changes related to increasing harvest pressure may place population at a higher risk of extirpation. Altogether, these results are especially relevant for maintaining populations at or above viable levels and must be considered in order to ensure the sustainability of the resource.
Keywords: Disturbance ecology; Landscape genetics; Phylogeography; Alien invasive species; Management; Selective harvest